Congenital Inflammatory Myopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Three patients with congenital inflammatory myopathy are reported from the Montreal Children's Hospital and Neurological Institute McGill University, Montreal, Canada. Seven additional cases are reviewed from the literature.